REGRESSION MODELS OF INDIVIDUAL LINEAR DIMENSIONS NECESSARY FOR CONSTRUCTING THE CORRECT FORM OF DENTAL ARCH IN YOUNG WOMEN WITH A WIDE FACE, DEPENDING ON THE FEATURES OF ODONTOMETRIC AND CEPHALOMETRIC INDICATORS - М. М. Shinkaruk-Dykovytska; T. P. Pozur; S. V. Koliadenko; V. O. Orlovskiy; G. M. Galunko (Український стоматологічний альманах)
The purpose of the study: build and analyze the regression models of computed tomographic parameters necessary to determine the correct shape of dental arches, depending on the odontological and cephalometric parameters for girls with normal occlusion close to orthognathic occlusion and a wide type of face.